High-strength high-thermal-conductivity silicon carbide supporting component and preparation method thereof
By strictly limited the granation of silicon carbide raw material granular grade and using ammonium polarotate to form a microporous, combined with the binding agent of oxidation and oxide and oxide, and epoxy resin or dihydrous phosphate to prepare high -intensity and high high strength high Thermal carbide supporting component has solved problems such as high sintering temperature and low high temperature resistance strength in existing technologies, and achieved efficient thermal guidance and antioxidant properties.
Patent Information
- Application Number
- CN202411406287.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The existing silicon carbide support members have problems such as high sintering temperature, low flexural strength at high temperature, low thermal shock stability, low thermal conductivity and low oxidation resistance.
By strictly limited silicon carbide raw materials granular granation, the use of granular accumulation and thermal treatment process to decompose to form a micropore, combined with oxide and oxidation burns and bisphenol A -type epoxy resin or liquid phosphate, aluminum aluminum The binding agent is performed by boosting and antihypertensive treatment to prepare high -intensity and high heat -conducting silicon support components.
The sintering temperature, high temperature resistance strength, high thermal shock stability, high thermal conductivity, and good antioxidant performance of silicon carbide support components.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of silicon carbide support components, and specifically relates to a high-strength and high-thermal-conductivity silicon carbide support component and a preparation method thereof. Background Art
[0002] Silicon carbide materials have the advantages of high mechanical strength, strong acid and alkali corrosion resistance, high thermal conductivity, good chemical stability, and small thermal expansion coefficient. Therefore, silicon carbide has been widely used as a supporting component in high-temperature kiln furniture, combustion chamber linings, heat treatment equipment and other fields.
[0003] At present, the main methods for preparing silicon carbide support components include solid phase sintering, liquid phase sintering, reaction sintering and recrystallization sintering. The silicon carbide support components prepared by different sintering processes have large performance differences, which has attracted the attention of technicians in this field:
[0004] The patented technology "A low-temperature sintered pure porous silicon carbide ceramic support and its preparation method (CN202410176849.8)" uses silicon carbide particles and silicon carbide precursors as raw materials. Although the prepared pure silicon carbide support has a low sintering temperature and high thermal conductivity, pure silicon carbide is easily oxidized at high temperatures, which reduces its service life.
[0005] The patented technology of "A silicon carbide ceramic membrane support and its preparation method (CN102389719A)" adopts recrystallization sintering technology, which utilizes the sublimation and re-condensation of small-sized silicon carbide particles at a high temperature above 2200°C to achieve the sintering effect, but it has disadvantages such as high sintering temperature and complex sintering process.
[0006] The patented technology "A method for preparing a low-temperature sintered acid- and alkali-resistant porous silicon carbide ceramic support (CN201710656733.4)" adopts an extrusion molding method and uses Suzhou clay, burned talc, chalk, fluorite and other minerals as sintering aids to prepare a silicon carbide support. Although the preparation process is simple and the sintering temperature is low, excessive liquid phase will lead to problems such as low thermal conductivity and low high-temperature flexural strength of the silicon carbide support.
[0007] The patented technology "A method for preparing porous silicon carbide support at low temperature (CN201610442510.3)" uses silicon carbide fine powder as the main raw material and introduces activated carbon powder as a pore-forming agent to prepare a silicon carbide support with good gas permeability and chemical stability, but there are still problems of insufficient thermal conductivity and low thermal shock stability.
[0008] In summary, the existing silicon carbide support components are limited by the composition and preparation method, and have problems such as high sintering temperature, low high-temperature flexural strength, low thermal shock stability, low thermal conductivity, and low oxidation resistance. Summary of the invention
[0009] The present invention aims to overcome the shortcomings of the prior art and has the objective of providing a method for preparing a high-strength and high-thermal-conductivity silicon carbide support component. The high-strength and high-thermal-conductivity silicon carbide support component prepared by this method has a low sintering temperature, high high-temperature flexural strength, high thermal shock stability, high thermal conductivity and good antioxidant performance.
[0010] To achieve the above purpose, the specific steps of the technical solution adopted by the present invention are:
[0011] Step 1, 10-20wt% of silicon carbide particles with a particle size of 1-2mm, 25-35wt% of silicon carbide particles with a particle size of 0.5-1mm, 10-20wt% of silicon carbide particles with a particle size of ≤0.5mm, 30-40wt% of silicon carbide fine powder with a particle size of ≤0.088mm, 1-3wt% of ammonium metavanadate, 1-2wt% of a sintering aid and 1-2wt% of a binder are prepared.
[0012] Step 2, according to the ingredients described in step 1, first add the silicon carbide particles with a particle size of 1 to 2 mm, the silicon carbide particles with a particle size of 0.5 to 1 mm, and the silicon carbide particles with a particle size of ≤0.5 mm into a mixer, then add 3 to 5 wt% of the ingredients of anhydrous ethanol, mix and grind for 8 to 12 minutes, and then add the silicon carbide fine powder, the ammonium metavanadate, the sintering aid and the binder in sequence, mix and grind for 10 to 15 minutes to obtain a mixture.
[0013] Step 3: placing the mixture in a mold, sealing it, and moving it to a pressure chamber of an isostatic press, first performing a pressure increase process, and then performing a pressure reduction process to obtain a green body of a silicon carbide support component.
[0014] Step 4: In an argon or nitrogen atmosphere, first heat treat the green silicon carbide support component at 800-1000° C. for 1-3 hours, and then heat treat it at 1300-1500° C. for 2-4 hours to obtain a high-strength and high-thermal-conductivity silicon carbide support component.
[0015] Chemical composition of the silicon carbide particles: SiC content ≥ 97.0wt%, Fe 2 O 3 The content of silicon carbide is ≤0.5wt%; the chemical composition of the silicon carbide fine powder is the same as that of the silicon carbide particles.
[0016] The ammonium metavanadate NH 4 VO 3The content is ≥99.0wt%.
[0017] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, wherein the molar ratio of yttrium oxide to lanthanum oxide is 1-1.2:1.
[0018] The binder is bisphenol A epoxy resin or liquid aluminum dihydrogen phosphate; wherein: the purity of the bisphenol A epoxy resin is ≥98.0wt%, and the FeO content of the liquid aluminum dihydrogen phosphate is ≤0.02wt%.
[0019] The pressure increasing process is: increasing the pressure to 25-40 MPa at a rate of 0.2-4.0 MPa / s, increasing the pressure to 50-70 MPa at a rate of 0.2-6.0 MPa / s, increasing the pressure to 80-100 MPa at a rate of 0.2-8.0 MPa / s, increasing the pressure to 110-130 MPa at a rate of 0.2-10.0 MPa / s, and increasing the pressure to 140-170 MPa at a rate of 0.5-8.0 MPa / s; maintaining the pressure for 1-5 minutes.
[0020] The pressure reduction process is: reducing the pressure to 110-130MPa at a rate of 0.2-5.0MPa / s, reducing the pressure to 80-100MPa at a rate of 0.2-10.0MPa / s, reducing the pressure to 50-70MPa at a rate of 0.2-8.0MPa / s, reducing the pressure to 20-40MPa at a rate of 0.2-6.0MPa / s, and reducing the pressure to 2MPa at a rate of 0.2-4.0MPa / s; unloading to normal pressure.
[0021] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:
[0022] (1) The present invention strictly limits the particle size distribution of silicon carbide raw materials and utilizes the particle accumulation and decomposition of ammonium metavanadate (2NH 4 VO 3 =V 2 O 5 +H 2 O+2NH 3 ) An appropriate amount of micropores are formed inside the material, and the high thermal conductivity and low thermal expansion coefficient of silicon carbide are utilized to make the prepared high-strength and high-thermal conductivity silicon carbide support component have high thermal shock stability.
[0023] (2) The present invention utilizes vanadium pentoxide formed by the decomposition of ammonium metavanadate during the heat treatment process to react with impurities in the silicon carbide raw material to form a vanadate liquid phase, thereby wrapping the silicon carbide particles in situ, avoiding oxidation of the silicon carbide particles during high-temperature use and maintaining their high thermal conductivity. The prepared high-strength and high-thermal-conductivity silicon carbide support component has good antioxidant properties and high thermal conductivity.
[0024] (3) The mixture of yttrium oxide and lanthanum oxide used in the present invention not only acts as a sintering aid to reduce the sintering temperature of the silicon carbide support component, but also increases the viscosity of the vanadate and silicate liquid phases at high temperatures, thereby increasing the firmness of the bonding between the raw material particles and significantly improving the high-temperature flexural strength of the silicon carbide support component. The prepared high-strength and high-thermal-conductivity silicon carbide support component has a low sintering temperature and high high-temperature flexural strength.
[0025] The high-strength and high-thermal-conductivity silicon carbide support component prepared by the present invention is tested to have a volume density of 2.92 to 3.10 g / cm 3 ; Thermal conductivity ≥100W / (m·K); High temperature flexural strength 15~20MPa (1200℃, 0.5h); Thermal shock stability ≥20 times (1100℃, air cooling); Oxide layer thickness ≤0.20mm (1400℃, 2h); Thermal expansion coefficient (20~1000℃) is (4.5-5.0)×10 -6 / ℃.
[0026] Therefore, the high-strength and high-thermal-conductivity silicon carbide support component prepared by the present invention has low sintering temperature, high high-temperature flexural strength, high thermal shock stability, high thermal conductivity and good oxidation resistance. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with specific implementation modes, but is not intended to limit the protection scope thereof.
[0028] A high-strength and high-thermal-conductivity silicon carbide support component and a preparation method thereof. The preparation method described in this specific embodiment is:
[0029] Step 1, 10-20wt% of silicon carbide particles with a particle size of 1-2mm, 25-35wt% of silicon carbide particles with a particle size of 0.5-1mm, 10-20wt% of silicon carbide particles with a particle size of ≤0.5mm, 30-40wt% of silicon carbide fine powder with a particle size of ≤0.088mm, 1-3wt% of ammonium metavanadate, 1-2wt% of a sintering aid and 1-2wt% of a binder are prepared.
[0030] Step 2, according to the ingredients described in step 1, first add the silicon carbide particles with a particle size of 1 to 2 mm, the silicon carbide particles with a particle size of 0.5 to 1 mm, and the silicon carbide particles with a particle size of ≤0.5 mm into a mixer, then add 3 to 5 wt% of the ingredients of anhydrous ethanol, mix and grind for 8 to 12 minutes, and then add the silicon carbide fine powder, the ammonium metavanadate, the sintering aid and the binder in sequence, mix and grind for 10 to 15 minutes to obtain a mixture.
[0031] Step 3: placing the mixture in a mold, sealing it, and moving it to a pressure chamber of an isostatic press, first performing a pressure increase process, and then performing a pressure reduction process to obtain a green body of a silicon carbide support component.
[0032] Step 4: In an argon or nitrogen atmosphere, first heat treat the green silicon carbide support component at 800-1000° C. for 1-3 hours, and then heat treat it at 1300-1500° C. for 2-4 hours to obtain a high-strength and high-thermal-conductivity silicon carbide support component.
[0033] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, wherein the molar ratio of yttrium oxide to lanthanum oxide is 1-1.2:1.
[0034] The binder is bisphenol A epoxy resin or liquid aluminum dihydrogen phosphate; wherein: the purity of the bisphenol A epoxy resin is ≥98.0wt%, and the FeO content of the liquid aluminum dihydrogen phosphate is ≤0.02wt%.
[0035] The pressure increasing process is: increasing the pressure to 25-40 MPa at a rate of 0.2-4.0 MPa / s, increasing the pressure to 50-70 MPa at a rate of 0.2-6.0 MPa / s, increasing the pressure to 80-100 MPa at a rate of 0.2-8.0 MPa / s, increasing the pressure to 110-130 MPa at a rate of 0.2-10.0 MPa / s, and increasing the pressure to 140-170 MPa at a rate of 0.5-8.0 MPa / s; maintaining the pressure for 1-5 minutes.
[0036] The pressure reduction process is: reducing the pressure to 110-130MPa at a rate of 0.2-5.0MPa / s, reducing the pressure to 80-100MPa at a rate of 0.2-10.0MPa / s, reducing the pressure to 50-70MPa at a rate of 0.2-8.0MPa / s, reducing the pressure to 20-40MPa at a rate of 0.2-6.0MPa / s, and reducing the pressure to 2MPa at a rate of 0.2-4.0MPa / s; unloading to normal pressure.
[0037] In this specific implementation mode:
[0038] Chemical composition of the silicon carbide particles: SiC content ≥ 97.0wt%, Fe 2 O 3 The content of silicon carbide is ≤0.5wt%; the chemical composition of the silicon carbide fine powder is the same as that of the silicon carbide particles.
[0039] The ammonium metavanadate NH 4 VO 3 The content is ≥99.0wt%.
[0040] This will not be described in detail in the embodiments.
[0041] Example 1
[0042] A high-strength and high-thermal-conductivity silicon carbide support component and a preparation method thereof. The preparation method described in this embodiment is:
[0043] Step 1, 10wt% of silicon carbide particles with a particle size of 1-2mm, 35wt% of silicon carbide particles with a particle size of 0.5-1mm, 20wt% of silicon carbide particles with a particle size of ≤0.5mm, 30wt% of silicon carbide fine powder with a particle size of ≤0.088mm, 1wt% of ammonium metavanadate, 2wt% of a sintering aid and 2wt% of a binder are prepared.
[0044] Step 2: Prepare the ingredients as described in step 1, first add the silicon carbide particles with a particle size of 1 to 2 mm, the silicon carbide particles with a particle size of 0.5 to 1 mm, and the silicon carbide particles with a particle size of ≤0.5 mm into a mixer, then add 3 wt % of the ingredients of anhydrous ethanol, mix and grind for 8 minutes, then add the silicon carbide fine powder, the ammonium metavanadate, the sintering aid and the binder in sequence, mix and grind for 10 minutes to obtain a mixture.
[0045] Step 3: placing the mixture in a mold, sealing it, and moving it to a pressure chamber of an isostatic press, first performing a pressure increase process, and then performing a pressure reduction process to obtain a green body of a silicon carbide support component.
[0046] Step 4: In an argon atmosphere, the green silicon carbide support component is first heat treated at 800° C. for 1 h, and then heat treated at 1300° C. for 2 h to obtain a high-strength and high-thermal-conductivity silicon carbide support component.
[0047] In this embodiment:
[0048] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, wherein the molar ratio of yttrium oxide to lanthanum oxide is 1:1.
[0049] The binder is bisphenol A epoxy resin with a purity of ≥98.0wt%.
[0050] The pressure increasing process is: increasing the pressure to 25MPa at a rate of 0.2MPa / s, increasing the pressure to 50MPa at a rate of 0.2MPa / s, increasing the pressure to 80MPa at a rate of 0.2MPa / s, increasing the pressure to 110MPa at a rate of 0.2MPa / s; and then increasing the pressure to 140MPa at a rate of 0.5MPa / s, and maintaining the pressure for 1 minute.
[0051] The depressurization process is: depressurizing to 130MPa at a rate of 0.2MPa / s, depressurizing to 100MPa at a rate of 0.2MPa / s, depressurizing to 70MPa at a rate of 0.2MPa / s, depressurizing to 40MPa at a rate of 0.2MPa / s, and depressurizing to 2MPa at a rate of 0.2MPa / s; unloading to normal pressure.
[0052] The high-strength and high-thermal-conductivity silicon carbide support member prepared in this embodiment was tested: the volume density was 2.92 g / cm 3 ; Thermal conductivity is 102.1W / (m·K); High temperature flexural strength is 19.8MPa (1200℃, 0.5h); Thermal shock stability is 25 times (1100℃, air cooling); Oxide layer thickness is 0.20mm (1400℃, 2h); Thermal expansion coefficient (20~1000℃) is 4.5×10 -6 / ℃.
[0053] Example 2
[0054] A high-strength and high-thermal-conductivity silicon carbide support component and a preparation method thereof. The preparation method described in this embodiment is:
[0055] Step 1, 15wt% of silicon carbide particles with a particle size of 1-2mm, 30wt% of silicon carbide particles with a particle size of 0.5-1mm, 17wt% of silicon carbide particles with a particle size of ≤0.5mm, 32wt% of silicon carbide fine powder with a particle size of ≤0.088mm, 2wt% of ammonium metavanadate, 2wt% of a sintering aid and 2wt% of a binder are prepared.
[0056] Step 2: Prepare the ingredients as described in step 1, first add the silicon carbide particles with a particle size of 1 to 2 mm, the silicon carbide particles with a particle size of 0.5 to 1 mm, and the silicon carbide particles with a particle size of ≤0.5 mm into a mixer, then add 4 wt% of the ingredients of anhydrous ethanol, mix and grind for 9 minutes, then add the silicon carbide fine powder, the ammonium metavanadate, the sintering aid and the binder in sequence, mix and grind for 12 minutes to obtain a mixture.
[0057] Step 3: placing the mixture in a mold, sealing it, and moving it to a pressure chamber of an isostatic press, first performing a pressure increase process, and then performing a pressure reduction process to obtain a green body of a silicon carbide support component.
[0058] Step 4: In an argon atmosphere, the green silicon carbide support component is first heat treated at 900° C. for 2 hours, and then heat treated at 1400° C. for 3 hours to obtain a high-strength and high-thermal-conductivity silicon carbide support component.
[0059] In this embodiment:
[0060] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, wherein the molar ratio of yttrium oxide to lanthanum oxide is 1.1:1.
[0061] The binder is bisphenol A epoxy resin with a purity of ≥98.0wt%.
[0062] The pressure increasing process is: increasing the pressure to 30MPa at a rate of 1.0MPa / s, increasing the pressure to 55MPa at a rate of 2.0MPa / s, increasing the pressure to 90MPa at a rate of 2.5MPa / s, increasing the pressure to 120MPa at a rate of 3.0MPa / s; and then increasing the pressure to 150MPa at a rate of 2.5MPa / s, and maintaining the pressure for 2 minutes.
[0063] The depressurization process is: depressurizing to 120MPa at a rate of 2.0MPa / s, depressurizing to 90MPa at a rate of 3.0MPa / s, depressurizing to 60MPa at a rate of 2.0MPa / s, depressurizing to 35MPa at a rate of 2.0MPa / s, and depressurizing to 2MPa at a rate of 1.0MPa / s; unloading to normal pressure.
[0064] The high-strength and high-thermal-conductivity silicon carbide support member prepared in this embodiment was tested: the volume density was 2.98 g / cm 3 ; Thermal conductivity is 113.2W / (m·K); High temperature flexural strength is 18.4MPa (1200℃, 0.5h); Thermal shock stability is 23 times (1100℃, air cooling); Oxide layer thickness is 0.18mm (1400℃, 2h); Thermal expansion coefficient (20~1000℃) is 4.7×10 -6 / ℃.
[0065] Example 3
[0066] A high-strength and high-thermal-conductivity silicon carbide support component and a preparation method thereof. The preparation method described in this embodiment is:
[0067] Step 1, 18wt% of silicon carbide particles with a particle size of 1-2mm, 27wt% of silicon carbide particles with a particle size of 0.5-1mm, 14wt% of silicon carbide particles with a particle size of ≤0.5mm, 37wt% of silicon carbide fine powder with a particle size of ≤0.088mm, 2wt% of ammonium metavanadate, 1wt% of a sintering aid and 1wt% of a binder are prepared.
[0068] Step 2: Prepare the ingredients as described in step 1, first add the silicon carbide particles with a particle size of 1 to 2 mm, the silicon carbide particles with a particle size of 0.5 to 1 mm, and the silicon carbide particles with a particle size of ≤0.5 mm into a mixer, then add 4 wt% of the ingredients of anhydrous ethanol, mix and grind for 10 minutes, then add the silicon carbide fine powder, the ammonium metavanadate, the sintering aid and the binder in sequence, mix and grind for 13 minutes to obtain a mixture.
[0069] Step 3: placing the mixture in a mold, sealing it, and moving it to a pressure chamber of an isostatic press, first performing a pressure increase process, and then performing a pressure reduction process to obtain a green body of a silicon carbide support component.
[0070] Step 4: In a nitrogen atmosphere, the green silicon carbide support component is first heat treated at 900° C. for 2 hours, and then heat treated at 14500° C. for 3 hours to obtain a high-strength and high-thermal-conductivity silicon carbide support component.
[0071] In this embodiment:
[0072] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, wherein the molar ratio of yttrium oxide to lanthanum oxide is 1.1:1.
[0073] The binder is aluminum dihydrogen phosphate, and the FeO content of the liquid aluminum dihydrogen phosphate is ≤0.02wt%.
[0074] The pressure increasing process is: increasing the pressure to 35MPa at a rate of 2.0MPa / s, increasing the pressure to 60MPa at a rate of 4.0MPa / s, increasing the pressure to 90MPa at a rate of 5.0MPa / s, increasing the pressure to 125MPa at a rate of 6.0MPa / s; and then increasing the pressure to 160MPa at a rate of 5.0MPa / s, and maintaining the pressure for 4 minutes.
[0075] The depressurization process is: depressurizing to 115MPa at a rate of 4.0MPa / s, depressurizing to 90MPa at a rate of 6.0MPa / s, depressurizing to 55MPa at a rate of 4.0MPa / s, depressurizing to 25MPa at a rate of 4.0MPa / s, and depressurizing to 2MPa at a rate of 3.0MPa / s; unloading to normal pressure.
[0076] The high-strength and high-thermal-conductivity silicon carbide support member prepared in this embodiment was tested: the volume density is 3.01 g / cm 3 ; Thermal conductivity is 113.2W / (m·K); High temperature flexural strength is 17.7MPa (1200℃, 0.5h); Thermal shock stability is 22 times (1100℃, air cooling); Oxide layer thickness is 0.17mm (1400℃, 2h); Thermal expansion coefficient (20~1000℃) is 4.9×10 -6 / ℃.
[0077] Example 4
[0078] A high-strength and high-thermal-conductivity silicon carbide support component and a preparation method thereof. The preparation method described in this embodiment is:
[0079] Step 1, 20wt% of silicon carbide particles with a particle size of 1-2mm, 25wt% of silicon carbide particles with a particle size of 0.5-1mm, 10wt% of silicon carbide particles with a particle size of ≤0.5mm, 40wt% of silicon carbide fine powder with a particle size of ≤0.088mm, 3wt% of ammonium metavanadate, 1wt% of a sintering aid and 1wt% of a binder are prepared.
[0080] Step 2: Prepare the ingredients as described in step 1, first add the silicon carbide particles with a particle size of 1 to 2 mm, the silicon carbide particles with a particle size of 0.5 to 1 mm, and the silicon carbide particles with a particle size of ≤0.5 mm into a mixer, then add 5 wt% of the ingredients of anhydrous ethanol, mix and grind for 12 minutes, then add the silicon carbide fine powder, the ammonium metavanadate, the sintering aid and the binder in sequence, mix and grind for 15 minutes to obtain a mixture.
[0081] Step 3: placing the mixture in a mold, sealing it, and moving it to a pressure chamber of an isostatic press, first performing a pressure increase process, and then performing a pressure reduction process to obtain a green body of a silicon carbide support component.
[0082] Step 4: In a nitrogen atmosphere, the green silicon carbide support component is first heat treated at 1000° C. for 3 hours and then heat treated at 1500° C. for 4 hours to obtain a high-strength and high-thermal-conductivity silicon carbide support component.
[0083] In this embodiment:
[0084] The sintering aid is a mixture of yttrium oxide and lanthanum oxide, wherein the molar ratio of yttrium oxide to lanthanum oxide is 1.2 to 1.
[0085] The binder is aluminum dihydrogen phosphate, and the FeO content of the liquid aluminum dihydrogen phosphate is ≤0.02wt%.
[0086] The pressure increasing process is: increasing the pressure to 40MPa at a rate of 4.0MPa / s, increasing the pressure to 70MPa at a rate of 6.0MPa / s, increasing the pressure to 100MPa at a rate of 8.0MPa / s, increasing the pressure to 130MPa at a rate of 10.0MPa / s; and then increasing the pressure to 170MPa at a rate of 8.0MPa / s, and maintaining the pressure for 5 minutes.
[0087] The depressurization process is: depressurizing to 110MPa at a rate of 5.0MPa / s, depressurizing to 80MPa at a rate of 10.0MPa / s, depressurizing to 50MPa at a rate of 8.0MPa / s, depressurizing to 20MPa at a rate of 6.0MPa / s, and depressurizing to 2MPa at a rate of 4.0MPa / s; unloading to normal pressure.
[0088] The high-strength and high-thermal-conductivity silicon carbide support member prepared in this embodiment was tested: the volume density was 3.10 g / cm 3 ; Thermal conductivity is 115.4W / (m·K); High temperature flexural strength is 15.3MPa (1200℃, 0.5h); Thermal shock stability is 20 times (1100℃, air cooling); Oxide layer thickness is 0.15mm (1400℃, 2h); Thermal expansion coefficient (20~1000℃) is 5.0×10 -6 / ℃.
[0089] Compared with the prior art, this specific implementation has the following positive effects:
[0090] (1) This specific embodiment strictly limits the particle size distribution of silicon carbide raw materials and utilizes the particle accumulation and decomposition of ammonium metavanadate (2NH 4 VO 3 =V 2 O 5 +H 2 O+2NH 3 ) An appropriate amount of micropores are formed inside the material, and the high thermal conductivity and low thermal expansion coefficient of silicon carbide are utilized to make the prepared high-strength and high-thermal conductivity silicon carbide support component have high thermal shock stability.
[0091] (2) This specific embodiment utilizes vanadium pentoxide formed by the decomposition of ammonium metavanadate during the heat treatment process to react with impurities in the silicon carbide raw material to form a vanadate liquid phase, thereby wrapping the silicon carbide particles in situ, avoiding oxidation of the silicon carbide particles during high-temperature use and maintaining their high thermal conductivity. Therefore, the high-strength and high-thermal-conductivity silicon carbide support component prepared by this invention has good oxidation resistance and high thermal conductivity.
[0092] (3) The mixture of yttrium oxide and lanthanum oxide used in this specific embodiment not only acts as a sintering aid to reduce the sintering temperature of the silicon carbide support component, but also increases the viscosity of the vanadate and silicate liquid phases at high temperatures, thereby increasing the firmness of the bonding between the raw material particles and significantly improving the high-temperature flexural strength of the silicon carbide support component. Therefore, the prepared high-strength and high-thermal-conductivity silicon carbide support component has a low sintering temperature and high high-temperature flexural strength.
[0093] The high-strength and high-thermal-conductivity silicon carbide support member prepared in this specific embodiment is tested: the volume density is 2.92-3.10 g / cm 3; Thermal conductivity ≥100W / (m·K); High temperature flexural strength 15~20MPa (1200℃, 0.5h); Thermal shock stability ≥20 times (1100℃, air cooling); Oxide layer thickness ≤0.20mm (1400℃, 2h); Thermal expansion coefficient (20~1000℃) is (4.5-5.0)×10 -6 / ℃.
[0094] Therefore, the high-strength and high-thermal-conductivity silicon carbide support component prepared in this specific embodiment has low sintering temperature, high high-temperature flexural strength, high thermal shock stability, high thermal conductivity and good oxidation resistance.
Claims
1. A method for preparing a high-strength and high-thermal-conductivity silicon carbide support member, characterized in that The steps of the preparation method are: Step 1, preparing ingredients according to 10-20wt% of silicon carbide particles with a particle size of 1-2mm, 25-35wt% of silicon carbide particles with a particle size of 0.5-1mm, 10-20wt% of silicon carbide particles with a particle size of ≤0.5mm, 30-40wt% of silicon carbide fine powder with a particle size of ≤0.088mm, 1-3wt% of ammonium metavanadate, 1-2wt% of a sintering aid and 1-2wt% of a binder; Step 2, according to the ingredients in step 1, first add the silicon carbide particles with a particle size of 1 to 2 mm, the silicon carbide particles with a particle size of 0.5 to 1 mm, and the silicon carbide particles with a particle size of ≤0.5 mm into a mixer, then add 3 to 5 wt% of the ingredients of anhydrous ethanol, mix and grind for 8 to 12 minutes, then add the silicon carbide fine powder, the ammonium metavanadate, the sintering aid and the binder in sequence, mix and grind for 10 to 15 minutes to obtain a mixture; Step 3, placing the mixture in a mold, sealing it, and moving it to a pressure chamber of an isostatic press, first performing a pressure increase process, and then performing a pressure reduction process, to obtain a green body of a silicon carbide support member; Step 4: In an argon or nitrogen atmosphere, first heat treat the green silicon carbide support component at 800-1000° C. for 1-3 hours, and then heat treat it at 1300-1500° C. for 2-4 hours to obtain a high-strength and high-thermal-conductivity silicon carbide support component.
2. A method for preparing a high-strength and high-thermal-conductivity silicon carbide support member according to claim 1, characterized in that The chemical composition of the silicon carbide particles is as follows: the content of SiC is ≥ 97.0wt%, and the content of Fe2O3 is ≤ 0.5wt%; the chemical composition of the silicon carbide fine powder is the same as that of the silicon carbide particles.
3. The method for preparing a high-strength and high-thermal-conductivity silicon carbide support member according to claim 1, characterized in that The content of NH4VO3 in the ammonium metavanadate is ≥99.0wt%.
4. The method for preparing a high-strength and high-thermal-conductivity silicon carbide support member according to claim 1, characterized in that The sintering aid is a mixture of yttrium oxide and lanthanum oxide, wherein the molar ratio of yttrium oxide to lanthanum oxide is 1-1.2:
1.
5. The method for preparing a high-strength and high-thermal-conductivity silicon carbide support member according to claim 1, characterized in that The binder is bisphenol A epoxy resin or liquid aluminum dihydrogen phosphate; wherein: the purity of the bisphenol A epoxy resin is ≥98.0wt%, and the FeO content of the liquid aluminum dihydrogen phosphate is ≤0.02wt%.
6. The method for preparing a high-strength and high-thermal-conductivity silicon carbide support member according to claim 1, characterized in that The pressure increasing process is: increasing the pressure to 25-40 MPa at a rate of 0.2-4.0 MPa / s, increasing the pressure to 50-70 MPa at a rate of 0.2-6.0 MPa / s, increasing the pressure to 80-100 MPa at a rate of 0.2-8.0 MPa / s, increasing the pressure to 110-130 MPa at a rate of 0.2-10.0 MPa / s, and increasing the pressure to 140-170 MPa at a rate of 0.5-8.0 MPa / s; maintaining the pressure for 1-5 minutes.
7. A method for preparing a high-strength and high-thermal-conductivity silicon carbide support member according to claim 1, characterized in that The pressure reduction process is: reducing the pressure to 110-130MPa at a rate of 0.2-5.0MPa / s, reducing the pressure to 80-100MPa at a rate of 0.2-10.0MPa / s, reducing the pressure to 50-70MPa at a rate of 0.2-8.0MPa / s, reducing the pressure to 20-40MPa at a rate of 0.2-6.0MPa / s, and reducing the pressure to 2MPa at a rate of 0.2-4.0MPa / s; unloading to normal pressure.
8. A high-strength and high-thermal-conductivity silicon carbide support member, characterized in that The high-strength and high-thermal-conductivity silicon carbide support member is a high-strength and high-thermal-conductivity silicon carbide support member prepared according to the method for preparing a high-strength and high-thermal-conductivity silicon carbide support member according to any one of claims 1 to 7.
Citation Information
Patent Citations
Silicon carbide ceramic support body and preparation method thereof
CN102389719A
A kind of method for preparing porous silicon carbide support body at low temperature
CN105884394B
A method for preparing a low-temperature sintered acid and alkali resistant porous silicon carbide ceramic support
CN107619281B
Low-temperature sintered pure porous silicon carbide ceramic support and preparation method thereof
CN118026718A
Preparation method of SiC / C3N4 / BiVO4 composite photocatalyst
CN109590009A